Media Pengenalan Safety Behavior untuk Anak Usia Dini - Hidayatulloh, M. Agung (Islamic Early Childhood Education Study Program, Faculty of Tarbiyah and Education, UIN Sunan Kalijaga Yogyakarta, 2019)
Early child is known as an individual who is vulnerable to a number of events that threaten his personal safety. These risks make the government of the Republic of Indonesia (RI) entrust teachers to teach early about safety behaviors. This article discusses the media that teachers use to introduce safety behaviors in early childhood. This qualitative study was conducted in four early childhood education units in Salatiga, Semarang, and Boyolali. Data collection techniques used were observation, interview, and documentation. It was stated that the teacher introduces safety behavior through the media that supports three children's learning styles, namely auditory, visual, and kinesthetic. The media are in the form of healthy walk, educative teaching aids (APE) of traffic, helmets, switches and sockets, scissors, oral, doormats and cloths, as well as pickup cards. The research findings imply that the introduction of safety behaviors should be adapted to the context.